Development of the athlete sleep behavior questionnaire: A tool for identifying maladaptive sleep practices in elite athletes - Driller, Matthew W; Mah, Cheri D; Halson, Shona L (Sleep Science, 2018)
Introduction: Existing sleep questionnaires to assess sleep behaviors may not be sensitive in determining the unique sleep challenges faced by elite athletes. The purpose of the current study was to develop and validate the Athlete Sleep Behavior Questionnaire (ASBQ) to be used as a practical tool for support staff working with elite athletes.Methods: 564 participants (242 athletes, 322 non-athletes) completed the 18-item ASBQ and three previously validated questionnaires; the Sleep Hygiene Index (SHI), the Epworth Sleepiness Scale (ESS) and the Pittsburgh Sleep Quality Index (PSQI). A cohort of the studied population performed the ASBQ twice in one week to assess test-retest reliability, and also performed sleep monitoring via wrist-actigraphy.Results: Comparison of the ASBQ with existing sleep questionnaires resulted in moderate to large correlations (r=0.32 - 0.69). There was a significant difference between athletes and non-athletes for the ASBQ global score (44±6vs. 41±6, respectively,p<0.01) and for the PSQI, but not for the SHI or the ESS. The reliability of the ASBQ was acceptable (ICC=0.87) when re-tested within 7 days. There was a moderate relationship between ASBQ and total sleep time (r=-0.42).Conclusion: The ASBQ is a valid and reliable tool that can differentiate the sleep practices between athletes and non-athletes, and offers a practical instrument for practitioners and/or researchers wanting to evaluate the sleep behaviors of elite athletes. The ASBQ may provide information on areas where improvements to individual athletes’ sleep habits could be made.
Keywords: Surveys and Questionnaires; Actigraphy; Polysomnography; Sleep Hygiene; Athletes